2015
DOI: 10.1093/humrep/dev089
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid autoimmunity, hypothyroidism and ovarian reserve: a cross-sectional study of 5000 women based on age-specific AMH values

Abstract: No external funding was used for this study. No conflicts of interest are declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
65
5
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 25 publications
4
65
5
5
Order By: Relevance
“…The results of these studies are variable. Polyzos et al for example did not observe an association between thyroid disorders and TAD, and low ovarian reserve as estimated by AMH levels [39]. Magri et al on the other hand found a negative influence of TAD on ART outcome in women with a normal ovarian reserve as depicted by high serum AMH levels [40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of these studies are variable. Polyzos et al for example did not observe an association between thyroid disorders and TAD, and low ovarian reserve as estimated by AMH levels [39]. Magri et al on the other hand found a negative influence of TAD on ART outcome in women with a normal ovarian reserve as depicted by high serum AMH levels [40].…”
Section: Discussionmentioning
confidence: 99%
“…Magri et al on the other hand found a negative influence of TAD on ART outcome in women with a normal ovarian reserve as depicted by high serum AMH levels [40]. Taking into consideration that one needs to be careful in extrapolating results from animal studies directly to the human condition, an explanation for the discrepancy among these studies may be that in the studies by Polyzos et al [39] and Magri et al [40] subclinical hypothyroidism prevailed while is the present study TSH concentrations were increased approximately 24-fold, indicative for a more severe disturbed thyroid function.…”
Section: Discussionmentioning
confidence: 99%
“…Since the pathophysiology of type 1 diabetes stems from autoimmune destruction of pancreatic β-cells, possible mechanisms include autoimmune disease. Previous studies that examined autoimmune oophoritis are few, although the presence of anti-ovarian antibodies is < 5% among women with type 1 diabetes (26), and AMH concentrations have not been associated with thyroid antibodies among women undergoing assisted reproduction procedures (27). To our knowledge, there are no studies that examine the possibility of autoimmune dysregulation at the hypothalamic-pituitary level.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, in a population of approximately 5,000 women attending a reproductive medicine center, Polyzos and colleagues examined the relationship between AMH and TSH as well as anti-thyroperoxidase antibodies. The authors concluded that in this large cohort of Belgian women hypothyroidism and thyroid autoimmunity disorders are not associated with low ovarian reserve (48). As there were differences in participant characteristics, as well as inconsistent findings between studies, additional prospective studies are clearly necessary to further elucidate the relationship between thyroid disorders and markers of ovarian reserve.…”
Section: Discussionmentioning
confidence: 80%